Synchronous Primary Carcinoma of Cervix and Ovary-A Rare Case Report - Abhijit Gajendra Bhanji; Pallavi Rishikesh Shah; Renuka Rajiv Kulkarni; Shailesh Sambhaji Desai (Journal of Clinical and Diagnostic Research, 2023)
Synchronous malignancies of female genital tract account for less than 3% of all genital tract neoplasms. Amongst synchronous tumours, ovarian with endometrial carcinoma accounts for 51.7% while ovarian with cervix accounts for less than 10% of them. Unusually, they have a favourable prognosis with 5 years survival rate being 73.3%. Authors hereby, present a case of 51-years-old female presented with bleeding per vagina and on examination cervical mass was detected. The cervical mass biopsy confirmed cribriform adenocarcinoma of cervix. Uterus and cervix could not be removed as it was FIGO (The International Federation of Gynecology and Obstetrics) stage III B (inoperable) thus was managed on chemotherapy and radiotherapy. A month later she presented with bilateral ovarian masses for which she had undergone bilateral oophorectomy and omentectomy. Histopathology confirmed moderately differentiated mucinous cystadenocarcinoma of bilateral ovaries. Thus a case of synchronous carcinoma of cervix and ovary was concluded. She tolerated all managements successfully.